Hydrophobicity and Adhesion of Aggregated Diamond Particles. Issue 5 (4th November 2020) - Yao, Kaili; Dai, Bing; May, Paul W.; Tan, Xiaojun; Han, Jiecai; Zhu, Jiaqi
Abstract : Diamond powders with high hydrophobicity are prepared by etching graphite plates using a hydrogen/argon (H2 /Ar) plasma. The morphology and size of the diamond powders are found to vary with the proportion of Ar in H2 from 0% to 50%. Wettability is measured using water contact angle (WCA) measurements giving values between 129.7° and 146.9°. The high hydrophobicity can be ascribed to the aggregated structure of the as‐grown diamond powders. To check this assumption, the aggregated diamond powders are separated into individual particles by mechanical grinding; then, the WCAs of separated as‐grown diamond powders and commercial dispersed diamond powders are compared. The separated diamond surfaces show the lower WCAs of 99.68° and 96.96°. The surface of the aggregated diamond powders also exhibits high adhesion to water. The diamond surface grown in 2% Ar suspends 40 μL of water under a tilt angle of 180°. Such aggregated diamond powders are promising for no‐loss liquid transportation. Abstract : Diamond powders with high hydrophobicity and adhesion can be prepared by etching graphite plates using a hydrogen/argon (H2 /Ar) plasma. The water contact angle of diamond powder grown from 2% Ar is 146.9°. The diamond surface can suspend 40 μL of water under a tilt angle of 180°. Such aggregated diamond powders are promising for no‐loss liquid transportation.